(untitled) (Comprehensive Journal of Science, 2025)
This study examines flash floods in Libya using Wadi Derna as a case study. It aims to model flood-hazard zones with GIS and DEM data and to assess the efficiency of existing protection systems. The results show that the basin is highly prone to flooding due to steep slopes, high drainage density and uncontrolled urban expansion within the valley, while dams and drainage structures suffer from design and maintenance deficiencies. The study proposes a set of engineering, planning and institutional measures—such as strengthening dams, redesigning urban drainage, enforcing floodplain zoning and developing early-warning systems—to reduce future flood impacts and enhance community resilience.